Anmerkungen zum Konzept einer „transkulturellen“ Geschichte in der deutschsprachigen Forschung - Höfert, Almut (Comparativ, 2008)
In the last few years, the term transcultural has been increasingly used in historiography. Since „culture“ can be understood in very different ways it is not self-evident which concept of culture transcultural refers to. With regard to currently prevailing usage and referring to the debate on transnational history, transcultural history is defined as an approach that considers the paradigm of civilisations explicitly to be a construct of the 9th century. Transcultural, therefore, is not meant to be a trendy substitute for intercultural. A transcultural approach rather aims to problematize “civilisation” as a unit of history.